2016
DOI: 10.1042/bst20150221
|View full text |Cite
|
Sign up to set email alerts
|

The sperm phospholipase C-ζ and Ca2+ signalling at fertilization in mammals

Abstract: A series of intracellular oscillations in the free cytosolic Ca(2+) concentration is responsible for activating mammalian eggs at fertilization, thus initiating embryo development. It has been proposed that the sperm causes these Ca(2+) oscillations after membrane fusion by delivering a soluble protein into the egg cytoplasm. We previously identified sperm-specific phospholipase C (PLC)-ζ as a protein that can trigger the same pattern of Ca(2+) oscillations in eggs seen at fertilization. PLCζ appears to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The OA is characterized by a sequence of morphological and molecular events that include cortical granule exocytosis, exit from M‐II arrest, extrusion of PB‐II, and formation of pronuclei (Xu et al, ; Swann and Lai, ). However, spontaneous oocyte activation (SOA) mimics all characteristics of OA process except formation of pronuclei and extrusion of PB‐II which might be due to insufficient increase of cytosolic free Ca ++ level (Cui et al, ; Premkumar and Chaube, ; Zhang et al, ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…The OA is characterized by a sequence of morphological and molecular events that include cortical granule exocytosis, exit from M‐II arrest, extrusion of PB‐II, and formation of pronuclei (Xu et al, ; Swann and Lai, ). However, spontaneous oocyte activation (SOA) mimics all characteristics of OA process except formation of pronuclei and extrusion of PB‐II which might be due to insufficient increase of cytosolic free Ca ++ level (Cui et al, ; Premkumar and Chaube, ; Zhang et al, ).…”
Section: Role Of Ca++ In Meiotic Resumption From Diplotene Arrestmentioning
confidence: 99%
“…Studies suggest that fertilizing spermatozoa trigger resumption of meiosis during oocyte activation (OA) by inducing Ca þþ release from internal stores (Swann et al, 2004;Whitaker, 2006;Machaca, 2007;Cui et al, 2013). The increased Ca þþ oscillations have been reported during sperm-induced OA and remain for several hours until pronuclei formation in several mammalian species (Vincent et al, 1992;Marangos et al, 2003;Wakai and Fissore, 2013;Ebner et al, 2015;Haverfield et al, 2016;Swann and Lai, 2016).…”
Section: Role Of Ca þþ In Meiotic Resumption From M-ii Arrestmentioning
confidence: 99%
“…The role of intracellular Ca 2+ and inositol 1,4,5-triphosphate (InsP 3 ) within the fertilized eggs has been at the forefront of recent research [19]. That signal transduction pathway involved in many biological processes, is first initiated by phospholipase C (PLC) isoforms, which hydrolyze the precursor phosphatidylinositol 4,5-biphosphate (PIP 2 ), resulting in the formation of InsP 3 and diacylglycerol (DAG).…”
Section: Physiological Mechanisms Involved In Egg Activationmentioning
confidence: 99%
“…Initial studies relied on the predominant hypothesis that the sperm activates the egg via binding to the egg membrane. Only later, researchers demonstrated that InsP 3 production and subsequent Ca 2+ oscillations are triggered by a sperm-derived soluble protein which is released to the oocyte cytoplasm immediately after sperm-egg fusion [19, 21]. …”
Section: Physiological Mechanisms Involved In Egg Activationmentioning
confidence: 99%
“…It may be possible that some cases of total fertilization failure that occur following ICSI treatment in the clinic could be a result of reduced levels of PLCζ in the patient's sperm. The clinical applications for PLCζ have been discussed thoroughly in a number of reviews (Ramadan et al 2012, Kashir et al 2012a, Nomikos et al 2013a, Swann & Lai 2016.…”
Section: Plcζ Is the Soluble Sperm Factor And Soafmentioning
confidence: 99%